2000
DOI: 10.1016/s0968-0896(99)00270-9
|View full text |Cite
|
Sign up to set email alerts
|

Monoalkylation of DNA by reductively activated FR66979

Abstract: AbstractÐThe antitumor antibiotic FR66979 has previously been shown to form interstrand cross-links in duplex DNA at the sequence [5 H -d(CG)] 2 , linking the exocyclic amino groups (N2) of deoxyguanosine (dG) residues. During the reaction of reductively activated FR66979 with DNA, products are formed which have electrophoretic mobility in denaturing polyacrylamide gels which is intermediate between that of unmodi®ed and interstrand cross-linked DNA. We show here that these products are monoadducts between FR6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
5
0
2
Order By: Relevance
“…Studies by Rajski and Williams [50-53] and by Hopkins and coworkers [54-58] have determined that FR900482 and FR66979 cross-link duplex DNA in the minor groove with the same 5′-CG-3′ sequence specificity as MMC. Both research groups demonstrated that the cross-link occurred on the N 2 exo -cyclic amino groups of the opposing guanidines.…”
Section: Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Rajski and Williams [50-53] and by Hopkins and coworkers [54-58] have determined that FR900482 and FR66979 cross-link duplex DNA in the minor groove with the same 5′-CG-3′ sequence specificity as MMC. Both research groups demonstrated that the cross-link occurred on the N 2 exo -cyclic amino groups of the opposing guanidines.…”
Section: Mode Of Actionmentioning
confidence: 99%
“…[55,58] These in vitro experiments included characterization of various intermediates and derivatives in the reaction cascade, [58] along with isolation and structural elucidation of the covalently cross-linked lesion by both FR900482 and FR66979 after reductive activation. [55] The latter experiment followed precepts introduced by Tomasz et al in the structure elucidation of MMC cross-linked DNA.…”
Section: Mode Of Actionmentioning
confidence: 99%
“…This duplex lacked suitable sites for formation of either intrastrand [32] or interstrand cross-links [2,30,31], suggesting that the monoadduct would be a terminal product. A double-stranded target was used because formation of monoadducts by other alkylating agents has been shown previously to be highly dependent on a duplex structure [33].…”
Section: Resultsmentioning
confidence: 99%
“…A descoberta da atividade antitumoral dos antibióticos FR900482 (9) e FR66979 (10), isolados de culturas de Streptomyces sandaensis, abriu uma nova perspectiva no tratamento do câncer 44 . Em estudos clínicos preliminares, FR-900482 (9) e o seu derivado acetilado FK-973 (11) foram três vezes mais potentes do que a mitomicina C (1), além de terem apresentado menor toxicidade 30,45,46 .…”
Section: Quinonasunclassified
“…Apesar de a função quinona não estar presente em sua estrutura, estes antibióticos antitumorais apresentam uma similaridade estrutural com a mitomicina C (1) e também requerem biorredução para exercerem sua atividade 30,[44][45][46][47] . Foi demonstrado que a redução destes antibióticos não leva à formação de ânion superóxido e este fato pode explicar a baixa toxicidade apresentada por tais substâncias 30 .…”
Section: Quinonasunclassified